Ideologi Feminisme dalam Video Klip Blackpink How You Like That - Dewanta, Anak Agung Ngurah Bagus Janitra Dewanta (Ruang Kata, 2025)
Feminism is a form of activity that requires balance or justice, as well as rights for women. Social inequality in terms of gender remains a topic of discussion to this day, South Korea is one of them. The purpose of this study is to understand feminism at the level of representation, reality, and ideology of Blackpink's video entitled How You Like That. How You Like That carries the theme of women's freedom, strength, and opposing those who look down on women. Although the theme of the Blackpink video does not explicitly address the issue of feminism, to identify the representation of feminist ideology in this video clip, the study uses John Fiske's semiotic analysis approach, The Codes of Television theory, and the method of observing, noting, and screenshots. The results of the study indicate three levels according to John Fiske's semiotics, namely reality, representation, and ideology. Furthermore, the level of representation shows women's freedom, self-existence, and self-confidence. Meanwhile, the ideology of the How You Like That video clip contains a form of feminism, especially post-modernism. This study shows that the symbols and signs contained in the video clip represent the ideology of post-modern feminism that creates a new, meaningful message, and provides positive energy to women to be able to fight discrimination. This research has succeeded in revealing the form of representation of Blackpink's feminist ideology in their video clip entitled How You Like That